Pediatric vancomycin dosing: Trends over time and the impact of therapeutic drug monitoring. (7th November 2014) - Balch, Alfred H.; Constance, Jonathan E.; Thorell, Emily A.; Stockmann, Chris; Korgenski, Ernest K.; Campbell, Sarah C.; Spigarelli, Michael G.; Sherwin, Catherine M.T.
Abstract Monitoring of vancomycin trough concentrations is recommended for pediatric patients in the product label and by several professional societies. However, among a network of freestanding children's hospitals vancomycin therapeutic drug monitoring (TDM) practices were reported to be highly variable. In this study, we sought to evaluate whether trends in vancomycin use and TDM changed across a large healthcare delivery system in Utah and Idaho from 2006 to 2012. Children ≤18 years who received ≥2 vancomycin doses were included. Overall, vancomycin TDM was performed during 5, 035 (80%) of 6, 259 hospital encounters, in which 85, 442 doses were administered and 7, 935 concentrations were obtained. Across this time period, the median trough concentration increased from 10.9 to 13.7 µg/mL (P < .001), which temporally coincided with recommendations published by the Infectious Disease Society of America that recommend targeting higher trough concentrations. Two or more abnormally low trough concentrations were accompanied by an increase in the dose 75% of the time. Similarly, ≥2 abnormally high trough concentrations were followed by a decrease in the dose 35% of the time. In aggregate, these data suggest that vancomycin TDM is commonly performed among children and the majority of abnormal trough concentrations were associated with an appropriate modification to the dosing regimen.